2013
DOI: 10.1073/pnas.1314992110
|View full text |Cite
|
Sign up to set email alerts
|

Why abundant tropical tree species are phylogenetically old

Abstract: Neutral models of species diversity predict patterns of abundance for communities in which all individuals are ecologically equivalent. These models were originally developed for Panamanian trees and successfully reproduce observed distributions of abundance. Neutral models also make macroevolutionary predictions that have rarely been evaluated or tested. Here we show that neutral models predict a humped or flat relationship between species age and population size. In contrast, ages and abundances of tree spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Another important empirical direction will be to extend this work across a broader range of taxa. For example, power law scaling of phylogenetic diversity with sample size for angiosperm communities (65) and nonneutrality in tropical forest phylogenies (66) suggest that the patterns we see here may not be restricted to microbes. Identifying the precise similarities and differences across taxonomic groups will undoubtedly lead to a range of insights and may also require more sophisticated analytical approaches given the relatively small size of many species-level phylogenies.…”
Section: Discussionmentioning
confidence: 85%
“…Another important empirical direction will be to extend this work across a broader range of taxa. For example, power law scaling of phylogenetic diversity with sample size for angiosperm communities (65) and nonneutrality in tropical forest phylogenies (66) suggest that the patterns we see here may not be restricted to microbes. Identifying the precise similarities and differences across taxonomic groups will undoubtedly lead to a range of insights and may also require more sophisticated analytical approaches given the relatively small size of many species-level phylogenies.…”
Section: Discussionmentioning
confidence: 85%
“…; Chisholm & Lichstein ; Condit et al ., ; Chave & Leigh ; Rosindell & Cornell , ; O'Dwyer & Green ; Vellend, ). Neutral theory has had considerably less success in predicting dynamic patterns of diversity, from decadal‐scale species abundance fluctuations to geological ages of species (Leigh, ; Wang et al ., ; Chisholm & O'Dwyer ). For example, in the case of rainforest trees, species ages predicted by neutral theory are sometimes older than the age of the Earth (Nee, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, several other studies report the opposite relationship of species in speciose clades suffering higher extinction risk (Schwartz & Simberloff, 2001;Davies et al, 2011). In addition, Wang et al (2013) reported that rare, putatively vulnerable species belong to phylogenetically young clades. However, also, clade-level traits often explain only a limited portion of the variance in species rarity or decline (Wang et al, 2013) and may be inconsistent among families (Sj€ ostr€ om & Gross, 2006;Davies et al, 2011).…”
Section: Imentioning
confidence: 98%
“…In addition, Wang et al (2013) reported that rare, putatively vulnerable species belong to phylogenetically young clades. However, also, clade-level traits often explain only a limited portion of the variance in species rarity or decline (Wang et al, 2013) and may be inconsistent among families (Sj€ ostr€ om & Gross, 2006;Davies et al, 2011).…”
Section: Imentioning
confidence: 99%